Advertising & IMC : principles & practice / Sandra Moriarty, University of Colorado Boulder, Nancy Mitchell, University of Nebraska-Lincoln, Charles Wood, University of Tulsa, William Wells, University of Minnesota. - Moriarty, Sandra E.(Sandra Ernst)author.
Revised edition of Advertising & IMC, [2015]